2015
DOI: 10.1111/jdv.13168
|View full text |Cite
|
Sign up to set email alerts
|

mTOR expression correlates with invasiveness and progression of extramammary Paget's disease

Abstract: microscopic examination: (i) in situ, (ii) invasive and (iii) lymph node. Twenty-four of the 52 specimens showed in situ lesions, 23 of the 52 specimens showed invasive lesions (Paget carcinoma) and five specimens showed lymph node metastases. Four patients died after metastasis to the lymph nodes and other organs.Invasive lesions and metastatic lymph nodes tended to have significantly higher mTOR expression than in situ lesions had, according to the Cochran-Mantel-Haenszel test (P < 0.01; Table 1).Mammalian t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, the high expression of phosphorylated ERK and phosphorylated AKT was also noted in 30 and 33% of EMPD patients without the HER2 overexpression, respectively, but with high Ki-67 labeling index ( 31 ). In addition, other studies have demonstrated that Ki-67, as well as mTOR, was expressed at significantly higher levels in invasive cases than carcinoma in situ cases ( 17 , 32 ). Furthermore, the DNA sequencing of EMPD study revealed that 19% of cases comprised mutant RAS or RAF genes and 35% of cases had mutations in PIK3CA (which encodes the catalytic subunit of PI3K) or AKT1 that activate those pathways ( 33 ).…”
Section: Her2–pi3k/erk Signaling In Empdmentioning
confidence: 91%
See 1 more Smart Citation
“…However, the high expression of phosphorylated ERK and phosphorylated AKT was also noted in 30 and 33% of EMPD patients without the HER2 overexpression, respectively, but with high Ki-67 labeling index ( 31 ). In addition, other studies have demonstrated that Ki-67, as well as mTOR, was expressed at significantly higher levels in invasive cases than carcinoma in situ cases ( 17 , 32 ). Furthermore, the DNA sequencing of EMPD study revealed that 19% of cases comprised mutant RAS or RAF genes and 35% of cases had mutations in PIK3CA (which encodes the catalytic subunit of PI3K) or AKT1 that activate those pathways ( 33 ).…”
Section: Her2–pi3k/erk Signaling In Empdmentioning
confidence: 91%
“…Metastasis is a multistage process that comprises tumor cell invasion, venous/lymphatic intravasation, transit in the vessels, venous/lymphatic extravasation, and proliferation at a new site ( 14 ). Recently, some studies have identified that the protein expression of molecules involved in proliferation and survival, including HER2 and mTOR, in the Paget cell (tumor cell of EMPD) is associated with invasiveness, metastasis, and OS ( 15 17 ). Similarly, translational research studies have demonstrated that cytokines, chemokines, and immune cells in EMPD confer favorable microenvironment for Paget cells to invade, migrate, and proliferate, thereby promoting metastasis ( 18 21 ).…”
Section: Invasive Extramammary Paget’s Disease (Empd) Therapeutic Chamentioning
confidence: 99%
“…Breslow thickness was classified using the minimum p value approach. 5 The optimal cut-off point was 6 mm (≤6 mm vs. >6 mm). Age was categorized as <55 years, 55-70 years and >70 years based on the rounded-off 33rd and 66th percentile values.…”
Section: S Kitamuramentioning
confidence: 99%
“…Further, mTOR is reported to be associated with malignancy in EMPD. 5 In this study, we investigate Drp1 and mTOR expression levels in EMPD through immunochemical analyses of clinical samples and analysed the correlation between the expression levels of Drp1 or mTOR and the clinical information. We found a positive correlation between the expression levels of Drp1 or mTOR and clinical stage of EMPD.…”
Section: Drp1 Expression Levels Correlate With Clinical Stage In Extrmentioning
confidence: 99%
See 1 more Smart Citation